Using sociotechnical theory to understand medication safety work in primary care and prescribers’ use of clinical decision support: a qualitative study - Aziz Sheikh; Justin Waring; Nde-Eshimuni Salema; Antony Chuter; Tony Avery; Mark Jeffries; Richard Neil Keers; Libby Laing; Azwa Shamsuddin (BMJ Open)
Objectives The concept of safety work draws attention to the intentional work of ensuring safety within care systems. Clinical decision support (CDS) has been designed to enhance medication safety in primary care by providing decision-making support to prescribers. Sociotechnical theory understands that healthcare settings are complex and dynamically connected systems of fluid networks, human agents, changing relationships and social processes. This study aimed to understand the relationship between safety work and the use of CDS.Design and setting This qualitative study took place across nine different general practices in England. Stakeholders included general practitioners (GPs) and general practice-based pharmacists and nurse prescribers. Semi-structured interviews were conducted to illicit how the system was used by the participants in the context of medication safety work. Data analysis conducted alongside data collection was thematic and drew on socio-technical theory.Participants Twenty-three interviews were conducted with 14 GPs, three nurse prescribers and three practice pharmacists between February 2018 and June 2020.Results Safety work was contextually situated in a complex network of relationships. Three interconnected themes were interpreted from the data: (1) the use of CDS within organisational and social practices and workflows; (2) safety work and the use of CDS within the interplay between prescribers, patients and populations; and (3) the affordances embedded in CDS systems.Conclusion The use of sociotechnical theory here extends current thinking in patient safety particularly in the ways that safety work was co-constituted with the use of CDS alerts. This has implications for implementation and use to ensure that the contexts into which such CDS systems are implemented are taken into account. Understanding how alerts can adapt safety culture will help improve the efficacy of CDS systems, enhance prescribing safety and help to further understand how safety work is achieved in primary care.